Images of the Emperors John II and Manuel I in the Accounts of William, Archbishop of Tyre - Pentek, Zdzisław (Studia Ceranea, 2021)
This article deals with the reception of the image of the Emperors John II and Manuel I of the Komnenos dynasty based on the chronicler’s account by William of Tyre (1130–1186). It shows a positive evolution in the portrayal of John II and his successor Manuel I, whom William met twice – in 1168 and when he stayed in Constantinople for seven months in 1179/1180. The image of Manuel I is positive, emphasizing the emperor’s positive qualities, such as generosity, wisdom, and justice.